If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 = 4(y + 6) + -7y Reorder the terms: 39 = 4(6 + y) + -7y 39 = (6 * 4 + y * 4) + -7y 39 = (24 + 4y) + -7y Combine like terms: 4y + -7y = -3y 39 = 24 + -3y Solving 39 = 24 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 39 + 3y = 24 + -3y + 3y Combine like terms: -3y + 3y = 0 39 + 3y = 24 + 0 39 + 3y = 24 Add '-39' to each side of the equation. 39 + -39 + 3y = 24 + -39 Combine like terms: 39 + -39 = 0 0 + 3y = 24 + -39 3y = 24 + -39 Combine like terms: 24 + -39 = -15 3y = -15 Divide each side by '3'. y = -5 Simplifying y = -5
| 4u+10=12 | | 8x-9=5x+219 | | 3x-17=4x+8 | | -4=-2-1 | | 3.5y=1.4x | | -18+x=2 | | x-5/x=5/9 | | -5+-2=x | | -4=-2-2 | | 4x/7=6/5 | | X/9-7x=7 | | -4=-2*-2 | | x/9=4/5 | | -[4x+(2x+5)]=8-(5x+1) | | 5(2l+7)=85 | | 15x-23=8x+12 | | 5p-3=2p+24 | | 280=(18-x)x+20x | | 104=38-3x | | x+50+10+x=180 | | (15x-23)+(8x+12)=180 | | 65+195(x-1)=2405 | | 0.35*x+1.6=-0.5 | | -71+5x=48-2x | | 4x+12=5x+9-x+3 | | -71+5c=48-2x | | 65+195x= | | (2x+7)+32=5x-15 | | -4=-1-4 | | 2a+3b+3c=74 | | 12x-153=2x+77 | | 11(y+4)=66 |